2008
DOI: 10.1039/b809075k
|View full text |Cite
|
Sign up to set email alerts
|

Template assisted electrodeposition of germanium and silicon nanowires in an ionic liquid

Abstract: In this paper we report for the first time on the room temperature template synthesis of germanium and silicon nanowires by potentiostatic electrochemical deposition from the air- and water stable ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide ([Py(1,4)]Tf(2)N) containing GeCl(4) and SiCl(4) as a Ge and Si source, respectively. Commercially-available track-etched polycarbonate membranes (PC) with an average nominal pore diameter of 90-400 nm were used as templates. Ge and Si nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 26 publications
0
82
0
1
Order By: Relevance
“…Избежать вза-имодействия кристаллизующегося Ge с H 2 O можно за счет использования ионных жидкостей [8] или расплавов солей германия [9]. Однако для формирования массивов наноструктур Ge из неводных электролитов необходи-мо использование поликарбонатных мембран [10], либо самоупорядоченных пористых матриц, например, оксида алюминия [11]. Более того, сформированные нанострук-туры Ge из неводных электролитов имеют аморфную структуру, поэтому после их формирования необходима термическая обработка, что также усложняет технологи-ческий процесс и ограничивает условия их применения.…”
Section: Introductionunclassified
“…Избежать вза-имодействия кристаллизующегося Ge с H 2 O можно за счет использования ионных жидкостей [8] или расплавов солей германия [9]. Однако для формирования массивов наноструктур Ge из неводных электролитов необходи-мо использование поликарбонатных мембран [10], либо самоупорядоченных пористых матриц, например, оксида алюминия [11]. Более того, сформированные нанострук-туры Ge из неводных электролитов имеют аморфную структуру, поэтому после их формирования необходима термическая обработка, что также усложняет технологи-ческий процесс и ограничивает условия их применения.…”
Section: Introductionunclassified
“…A less extensive examination of a possible crystallization during heat treatment, without the effort of HR TEM investigations, is Raman spectroscopy [30]. This non destructive characterization method allows a fast investigation of the Raman crystallinity.…”
Section: Raman Investigationmentioning
confidence: 99%
“…Complementary and an other proof of the non crystallinity is Raman spectroscopy (30).1nvesti gations are carried out using the same -150 nm thick RFS deposited amorphous layers investigated by AfM analysis in Section 333. Fig.…”
Section: Structural Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…36,[41][42][43][44][45][46] Ge electroplating has also been reported on semiconducting substrates such as Si. 47 There are some reports on the formation of thick Ge nanostructures, [48][49][50] which showed that, depending on potential, Ge nanostructures can be grown from aqueous solution by dissolution into and saturation of a liquid Hg electrode.…”
mentioning
confidence: 99%